Desiderata Geotechnica - Wu, Wei.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book presents contributions to a workshop dedicated to Prof. Gerd Gudehus on the occasion of his 80th birthday and held in Vienna, Austria, on 14-16 August 2018. The articles gathered here, many of which were written by former students, friends and colleagues of Prof. Gudehus, cover diverse topics that reflect the breadth and depth of geomechanics research. Consequently, they offer a valuable source of ideas and inspiration on areas ranging from sophisticated constitutive models to advanced numerical methods, from particles to continua, and from fractals of geomaterials to the design of offshore wind turbine foundations. .
Keywords: Engineering geology; Geotechnical engineering; Geoengineering; Geotechnical Engineering and Applied Earth Sciences